Augmented shelf-life and regeneration competence of activated charcoal (AC) supplemented synthetic seeds in Cymbidium pendulum (Roxb.) Sw. - Pehwal, Anju; Vij, Suraj Prakash; Pathak, Promila; Attri, Lucky K (Current Botany, 2013)
A protocol for their long term storage at low temperature has been developed using synthetic seeds technology in Cymbidium pendulum (Roxb.)Sw. in present piece of work. This species is known as an important ornamental and medicinal orchid. Protocorm Like Bodies (PLBs) were used as propagules for encapsulation. They were raised on Basal M medium [1], in addition with inorganic plant growth regulators such as [Indole-3-acetic acid (IAA); Indole-3-butyric acid (IBA) and Naphthalene acetic acid (NAA); 6-Benzyl amino purine (BAP); Kinetin (KN) at 1mg/l concentrations. Different combinations were compared for their efficacy in supporting large scale production of elite propagules for encapsulation. Among these NAA proved to be the best as it supported 99.5% of asymbiotic seed germination in to largest PLBs (2.2mm) with highest chlorophyll content at 2.15µg/mg. PLBs were encapsulated in 3% sodium alginate and di-hydrated salt calcium chloride (100mM). Resultant synthetic seeds were observed for their viability after different period of storage at 250C and 40C. Role of AC if added to nutrient matrix in extended storage of synthetic seeds with better conversion at mass scale has been the main focus of the study. Interestingly, AC supplemented synthetic seeds could be stored for 480 days with 10.5% conversion and showed fairly good regeneration or production of secondary PLBs.